Enhancing Students’ Environmental Awareness through Curriculum-Based Instruction on Biodegradation Processes - Nwabuwe, Henrietta Ifeanyichukwu; Fidelis, Anyima Friday (dialektika kontemporer, 2025)
Environmental degradation remains a global concern, with biodegradation emerging as a sustainable approach to mitigating pollution. However, science education curricula in many developing countries inadequately address the concept of biodegradation, resulting in limited environmental awareness among students. This study investigated the effectiveness of curriculum-based instruction on biodegradation processes in enhancing environmental awareness among undergraduate science students in Nigeria. A quasi-experimental design with pre-test and post-test control groups was employed. A total of 120 students (60 experimental, 60 control) participated in the study across two public tertiary institutions. The experimental group received structured instruction on biodegradation over four weeks using interactive and inquiry-based methods, while the control group continued with the conventional curriculum. Data were collected using a validated Environmental Awareness and Biodegradation Instruction Survey (EABIS) and analyzed using paired and independent sample t-tests. Results indicated a statistically significant improvement in the environmental awareness of the experimental group compared to the control group (p < 0.001). The findings demonstrate that integrating biodegradation topics into science education fosters students’ cognitive understanding and promotes environmentally responsible attitudes and behaviors. The study underscores the need for science curriculum reform and pedagogical innovation to include real-world environmental issues such as waste management and microbial degradation. It concludes that curriculum-based environmental education is an effective strategy for building ecological literacy and empowering students to contribute meaningfully to sustainable development. Recommendations are offered for educators, curriculum developers, and policymakers to enhance environmental education at the tertiary level.